Investigating electric field induced molecular distortions in polypropylene using Raman spectroscopy - Vetter, Marleen; Healy, Matthew J. F.; Lane, David W. (Elsevier, 2020)
Polymeric electric insulators are an integral part of many electronic circuits and systems. Changes induced by an electric field can affect various mechanisms; including electrical polarisation and electromechanical properties. Changes in the dielectric material can be tracked using spectroscopic methods. This study has shown that analysing polypropylene under electric field stress using Raman spectroscopy in combination with principal component analysis allows small changes in the non-crystalline phase to be identified. We have observed that for polypropylene, vibrational motion and changes in conformation occur mostly within the tie molecules connecting the overall cluster network. Amorphous molecular chains in the spherulites were also found to orient and form into a smectic mesophase. These electromechanical changes at the micro- and macromolecular level were found to be generally reversible once the stress is removed. However, with increased aging, these changes may lead to adverse structural changes and thus, in the future, this information may be used to inform faults and defect detection within polymeric dielectric materials.
Keywords: Electric field stress; Principal component analysis; Raman spectroscopy; Polypropylene